PENGARUH KORUPSI DAN POLITIK TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PERSPEKTIF ISLAM - Sandi Mulyadi (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2023)
This study aims to analyze the influence of corruption and political conditions on economic growth in Indonesia from 2000-2021 with an Islamic economic perspective. The variables examined in this study include economic growth, corruption which is explained by the proxy value of control of corruption, and politics which is proxied by the value of political stability. This study uses annual secondary data in Indonesia with a research period from 2000 to 2021 using linear regression analysis using the OLS method. The research results show that the variables of corruption and politics have an effect on economic growth. The implications of this research suggest that the Indonesian government continues to control and properly control corruption and maintain political stability so that economic growth will improve.Keywords: Corruption, Politics, Economic Growth